Terms in context - Pearson, Jennifer (Studies in corpus linguistics, 1998)
Terms in Context applies the methodology that has been developed over the last two decades in corpus linguistics to the relatively new and still little developed field of corpus-based terminography. While corpora are already being used by some terminologists for the identification of terms and retrieval of contextual fragments, this book describes the first attempt to use corpora for terminography in much the same way as large general reference corpora are already being used for general language lexicography. The author goes beyond the standard problem of identifying terms as opposed to non-te.